Colonial women missionaries of the Committee for Women's Work, 1861-1967. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2013)
Originally the "Ladies' Association for the Promotion of Female Education in India and other Heathen Countries", a semi-autonomous body linked with the Society for the Propagation of the Gospel in Foreign Parts. In 1895 this became the "Womens' Missionary Association for the Promotion of Female Education in the Missions of the SPG", and in 1904 an SPG Committee for Women's Work was established, responsible to the Standing Committee. Includes minutes of main and sub-committees, candidates' books, in and out letters, and reports. This collection is organised by subject and date; the correspondence is divided according to whether it is an original or a copy and whether it has been sent or received, it is also organised by date. This digital collection currently comprises approximately two thirds of the vast records relating to the Committee on Women's Work stored at Rhodes House Library, Oxford.
Date range: 1861-1967.
Keywords: Women missionaries; Society for the Propagation of the Gospel in Foreign Parts (Great Britain). -- Ladies' Association for the Promotion of Female Education among the Heathen; Missions -- Societies, etc. -- Early works to 1800.